The mediating role of thriving at work between organizational inducements and work outcomes - Karadaş, Georgiana; Vatankhah, Sanaz; Ozturk, Anastasia; Altun, Özlem (John Wiley and Sons Inc, 2024)
The study intends to assess the underlying mechanism of thriving between organizational inducements (OIs) and health care workers’ (HCWs) mental health and work effort based on social exchange theory and the socially embedded model (SEM) of thriving. This study tested a conceptual model regarding the antecedents and outcomes of thriving at work (TW). According to the results of structural equation modelling, both dimensions of OIs predict TW among HCWs. Employees who receive OIs display enhanced levels of thriving, which plays a key role in HCWs’ mental health and their work effort. This research adds important insights to the thriving literature by empirically examining its mediating role between workplace resources and HCWs’ health and work-related outcomes. © 2023 John Wiley & Sons Ltd.
Keywords: conceptual framework; health worker; mental health; numerical model; organization; social theory